Chloroplast Electron Chain, ROS Production, and Redox Homeostasis Are Modulated by COS-OGA Elicitation in Tomato (Solanum lycopersicum) Leaves - Moreau, Sophie; van Aubel, Géraldine; Janky, Rekin’s; Van Cutsem, Pierre (Frontiers in Plant Science, 2020)
The stimulation of plant innate immunity by elicitors is an emerging technique in agriculture that contributes more and more to residue-free crop protection. Here we used RNA-Sequencing to study gene transcription in tomato leaves treated three times with the COS-OGA elicitor FytoSave® that induces plants to fend off against biotrophic pathogens. Results showed a clear up-regulation of sequences that code for chloroplast proteins of the electron transport chain, especially PSI and ferredoxin. Concomitantly, stomatal conductance decreased by half, NAD(P)H content and ROS production doubled but fresh and dry weights were unaffected. Chlorophyll, β-carotene, violaxanthin and neoxanthin contents decreased consistently upon repeated elicitations. Fluorescence measurements indicated a transient decrease of the effective PSII quantum yield and a non-photochemical quenching increase but only after the first spraying. Taken together, this suggests that plant defense induction by COS-OGA induces a long-term acclimation mechanism and increases the role of the electron transport chain of the chloroplast to supply electrons needed to mount defenses targeted to the apoplast, without compromising biomass accumulation.